Peer Teaching Model with Youtube Media as an Effort to Improve Maharah Kalam of Class VII Students at Al-Hamidiyah Junior High School Palembang - Rohaida, Astini; Sabana, Rendi; Jumhur, Jumhur; Karsa, Rangga Adi; Alhajj, Ahmad Fadhil (Journal of English Language and Education, 2025)
This study aims to improve students’ speaking skills (maharah kalam) in Arabic language learning through the implementation of a peer teaching model supported by YouTube media. The background of the study stems from students' lack of confidence in speaking Arabic and the predominance of conventional teaching methods in schools. A mixed-method approach was employed, combining qualitative and quantitative methods with data collected through observation, interviews, tests, documentation, and questionnaires. The research subjects were seventh-grade students at SMP Al-Hamidiyah Palembang. The findings reveal that the application of the peer teaching model supported by YouTube media significantly enhanced students' speaking abilities. This was evidenced by the improvement in pre-test and post-test scores, and further supported by statistical analyses (normality test, homogeneity test, and paired sample t-test) confirming the method's effectiveness. Collaboration in small groups, along with engaging visual media, fostered an interactive and enjoyable learning environment that boosted students’ confidence and active use of the Arabic language. Therefore, this model is recommended as an effective strategy for developing speaking skills in Arabic language education.